Kelas Ibu Hamil Di Desa Loru Kecamatan Sigi Biromaru - Enggar Enggar; Mas’ul Lembah; Amanda Amanda; Arie Maineny (Pusat Riset dan Inovasi Nasional, 2023)
Quality antenatal care is essentially one of the basic medical services that is very strategic in an effort to improve the health status of pregnant women and the fetuses they contain. To achieve this desire, it is necessary to always pay attention to access to antenatal services that can be reached by pregnant women and their families, so that pregnant women can continue to attend antenatal check-ups on an ongoing basis for the health and safety of their pregnancy. Apart from that, the quality of the services provided must always be maintained, thereby increasing the continuity of antenatal checks so that partners can maintain the health status of the pregnancy and early detection of disorders that may occur during pregnancy (Guidelines for Antenatal Services).